Circuit troubleshooting handbook - Lenk, John D. (McGraw-Hill, 1999)
This valuable problem-solving guide puts in your hands the power you need today to resolve faults in and coax peak performance from new, experimental, or just plain temperamental circuits. Written by one of the bestselling practical electronics authors of all timeÑhis books have sold more than 2 million copies in 9 languages worldwideÑThe Electronic Troubleshooting Handbook, Volume I, gives you full descriptions of the operation of important circuits, and it shows you how each circuit's characteristics may figure in its failure or poor performance. Without abstract theory or complicated math, this book gives you the clear explanations and hands-on troubleshooting procedures that will quickly point you toward the villain in malfunctions in circuits from op-amp to data conversion to OTA. No other book offers such complete and to-the-point guidance in troubleshooting today's circuits. It's an electronic circuit problem-solving kit between covers.